Educational program to promote the self-care of people with diabetes mellitus - Maria Gabriela Secco Cavicchioli; Tarcila Beatriz Ferraz de Campos; Anderson da Silva Rosa; Edvane Birelo Lopes De Domenico; Giovana Andrade Frederico; Odete de Oliveira Monteiro; Mônica Antar Gamba (Universidad Nacional de Colombia, 2019)
Objective: to evaluate the effect of an intervention program on the capacity and action for the self-care of people with diabetes mellitus. Method: this is an intervention study with the implementation of a problem-solving educational program in diabetes in a private health service. Capacity and action scales were applied for the self-care, in the initial moment and after the  intervention with analysis of the outcome by the metabolic control. Differences were identified by the Student t test and the comparison of the scales variability calculated by Cronbach's alpha, with a 95 % confidence interval. Results: participated in the study 23 people, with significant improvement in the values of glycated hemoglobin, glycemic and diastolic blood pressure variability after the educational program. The educational strategy in diabetes provided improvement in both capacity and action for self-care, respectively (p ≤ 0.0 %), Cronbach's alpha initial 0.895 and final 0.938  Conclusion: education programs using participatory methodologies are essential to enable the person with diabetes to manage and monitor the disease.